2014
DOI: 10.1002/app.41336
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrrole‐silk electro‐conductive composite fabric byin situchemical polymerization

Abstract: This article describes the preparation of polypyrrole-silk composite fabric by in situ chemical polymerization of pyrrole. In situ polymerization process has been optimized by employing Box-Behnken response surface design. The effect of process parameters on surface resistivity of the fabric has been statistically analyzed. Most significant process parameter and interaction effects have been identified. Thermal, electrical, and morphological properties of the composite fabric have been studied. Surface resisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 32 publications
4
29
0
Order By: Relevance
“…Literature says that in situ polymerization methods are very suitable for applications of conductive polypyrrole to textiles [12][13][14][15][16][17]. These electroconductive textiles are proposed to be used in various applications such as heating pads [3], EMI shielding [16,17], and sensors [2,14,15]. There are few works reported in the literature regarding sensory applications of polypyrrole polymers in pure form or embedded in other structures [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Literature says that in situ polymerization methods are very suitable for applications of conductive polypyrrole to textiles [12][13][14][15][16][17]. These electroconductive textiles are proposed to be used in various applications such as heating pads [3], EMI shielding [16,17], and sensors [2,14,15]. There are few works reported in the literature regarding sensory applications of polypyrrole polymers in pure form or embedded in other structures [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…are a class of organic conductive material which have electrical conductivity just below of metals. These ICPs can be successfully coated on textile fabric to prepare flexible and durable electro‐conductive fabrics . It is found that PPy has favorable application in the EMI shielding due to its good electrical conductivity and outstanding atmospheric stability .…”
Section: Introductionmentioning
confidence: 99%
“…Only report available on PPy coated polyester spunlace nonwoven fabrics and which is found useful for EMI shielding in the frequency range 100–800 MHz with efficiency of 37 dB . In fact, it has been revealed that porous and bulky textile structures have more potential of PPy add‐on . Higher PPy add‐on may lead to better electrical conductivity and EMISE.…”
Section: Introductionmentioning
confidence: 99%
“…But naturally the processing of these yarns or fabrics is difficult and they lose the textile properties. Many such limitations associated with processability, low mechanical strength and poor flexibility can be successfully overcome by coating/applying conducting polymers on strong and flexible textile substrates [1,[9][10][11]. Conductive polymers, used to fill or coat fibers, show electrical properties due to their conjugated double bond chain structures [12].…”
Section: Introductionmentioning
confidence: 99%
“…Polypyrrole is successfully coated on different textile fibres such as cotton, wool, silk, polyester etc. and their various applications are explored by different researchers [9][10][11][12][13]. So, the trend is of making conductive textiles by coating conductive polymer and characterizing their functional properties to meet demand of technical applications.…”
Section: Introductionmentioning
confidence: 99%